2021
DOI: 10.1080/1331677x.2021.1952086
|View full text |Cite
|
Sign up to set email alerts
|

Female presence in corporate governance, firm performance, and the moderating role of family ownership

Abstract: Assessing the role of diversity in corporate governance has attracted growing interest. In addition, significant relationships are expected between diversity dimensions and firm performance. This research aims to analyze the relationships between female presence in corporate board-firm financial performance and the extent to which such influence is moderated by family ownership. The study's sample, based on the listed firms on the Pakistan Stock Exchange (PSX), represents the nonfinancial sector from 2008 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 77 publications
6
34
0
2
Order By: Relevance
“…Moreover, Halcro et al (2021) conclude that smaller companies are more driven to grow, showing that larger companies have worse performances. Other studies failed to identify a significant relationship between size and corporate performance (e.g., Amin et al, 2021;Arioglu, 2021;Kagzi and Guha, 2018;Proença et al, 2020).…”
Section: Company Sizementioning
confidence: 99%
“…Moreover, Halcro et al (2021) conclude that smaller companies are more driven to grow, showing that larger companies have worse performances. Other studies failed to identify a significant relationship between size and corporate performance (e.g., Amin et al, 2021;Arioglu, 2021;Kagzi and Guha, 2018;Proença et al, 2020).…”
Section: Company Sizementioning
confidence: 99%
“…Gender significantly differs in some aspects of leadership style (Oshagbemi & Gill, 2003). The involvement of women in corporate governance is positively linked to a company's financial performance (Amin et al, 2021). Companies with gender-diverse leaders are more effective at implementing environmentally friendly strategies than other companies (Glass et al, 2016).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Female directors are less thirsty for power, more diligent in overseeing and controlling certain processes, and more concerned with the quality of financial reporting [13,14]. As Adams et al [15] and Amin et al [16] pointed out, from the perspective of investors the presence of women managers and their independence on the board are factors that enhance the future performance of the business. Elliott and Smith [6] showed that women on the board are more likely to push for more women to lead, and Adusei et al [17] demonstrated the positive and statistically significant relationship between the board gender diversity and management gender diversity.…”
Section: Introductionmentioning
confidence: 99%